A literature review of the factors limiting the application of BIM in the construction industry - Sun, Chengshuang; Jiang, Shaohua; Skibniewski, Miroslaw J.; Man, Qingpeng; Shen, Liyin (Technological and Economic Development of Economy, 2017)
Building Information Modeling (BIM) has had a profound effect on the construction industry. It has greatly improved coordination among stakeholders, enhanced productivity, and increased profits. However, many factors still limit the application of BIM in the construction industry. This study conducts a literature review to identify these negative factors. Firstly, twenty-two sub-factors are identified and classified into five categories: Technology, Cost, Management, Personnel, and Legal. Secondly, some suggestions for eliminating these limiting factors are given. Finally, the study also identifies further research directions for improving BIM theory and applying BIM technology widely and successfully. The results of this study will provide support for practitioners who are using or plan to use BIM. First published online: 03 Nov 2015